DIFFERENTIAL APPROACH OF CONTINUOUS AND INTERMITTENT RENAL REPLACEMENT THERAPY APPLYING IN CARDIAC SURGERY ACUTE KIDNEY INJURY - K. Zakon; V. Romanova; V. Dudarenko; I. Arbuzova; G. Radchenko (Ukrainian Journal of Nephrology and Dialysis, 2016)
Background: In-hospital mortality of cardiac surgery patients with AKI is 3-7 times higher than those without AKI. This prospective observational study was dedicated to evaluate a differential approach ofapplying continuous and intermittent modalities of RRT in cardiac surgery patients.Methods. One hundred and six adult cardiac surgery patients admitted hospital in 2008-2011 years, who had AKI and met inclusion criteria were allocated in CRRTor IRRTgroup.Results. Observed in-hospital mortality of CRRT patients was significantly lower than predicted by APACHE II (р=0,01), in contrast with IRRT group. The in-hospital mortality of cardiac surgery patients with AKI and multiorgan dysfunction treated with CRRT was significantly lower than in patients treated with IRRT (32,5% vs 67,6%, р=0,012) and lower than predicted by APACHE II (32,5% vs 50%, р=0,025), while in IRRT group observed in-hospital mortality was significantly higher (67,6% vs 46%, р=0,012) than predicted.Discussion. The complexity of the treatment of cardiac surgery patients with AKI and, especially, the subset with critical illness, could explain the lack of association between RRT modality and renal recovery and the in-hospital mortality of whole cohort, as well. This is a basis for differential and complementary applying ofdifferent RRT modalities according to the specific clinical situation.Conclusions. Differential applying of continuous RRT modalities for the treatment of cardiac surgery patients withAKI, as a component of MOF, and intermittent RRT for the patients, who have not multiorgan dysfunction, could contribute to reducing in-hospital mortality in this cohort.